Brown Dog Tick, Rhipicephalus sanguineus Latreille (Arachnida: Acari: Ixodidae) - Cynthia C. Lord (EDIS)
The brown dog tick, Rhipicephalus sanguineus Latreille, is unusual among ticks, in that it can complete its entire life cycle indoors. Because of this, it can establish populations in colder climates, and has been found in much of the world. Many tick species can be carried indoors on animals, but cannot complete their entire life cycle inside. Although R. sanguineus will feed on a wide variety of mammals, dogs are the preferred host in the US and appear to be required to develop large infestations. This document is EENY-221, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: July 2001.